Attitudes of the Lao People towards the New Normal During the Outbreak of the Covid-19 - INDAVONG, Dalounny; SIFONGXAY, Sangthong; SISOULAT, Davone; Somkith , Somkith; CHITTAPHONE , Namfonh; PHENGSAVAT, Sitthivikone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this research were: 1) to study Laos peoples’ cognitive of the Covid-19, 2) to study Laos peoples’ behavior towards the Prevention of Covid-19 and 3) to study Lao people’s opinion on the new normal during the covid-19 epidemic. The samples were 690 Lao peoples who live in Laos by using an online questionnaire from Google form. The Cronbach alpha reliability coefficient was 0.922. Statistical methods used in data analysis were descriptive statistics such as the frequency, percentage, mean and standard deviation. The major findings found that: The attitude of Lao people on new normal during the Covid-19 pandemic Lao peoples had the most accurate knowledge of Covid-19 and prevention of Covid-19, there were good self-defense behaviors and there a new normal during the pandemic wearing a mask (Mas) when going out, avoiding contact with vulnerable groups or people who are sick, avoiding contact with others, washing your hands every time with 90% alcohol by volume when handling things in public, eating nutritious food, avoiding eating raw food. Masks and alcohol sprays have been found to be effective in protecting the body from COVID-19 and preventing the virus from spreading to other people, which is becoming more common. In terms of health or self-care to prevent COVID-19, it was found that Lao people have reduced their outreach to society and have turned to living and working at home and having more time for their families. In terms of economically, Lao people will be more disciplined in spending their money, concerned with spending their money and many businesses will have checkpoints for customers before entering the shops, and they will have hand sanitizer before entering the shops too.